2007
DOI: 10.1097/pdm.0b013e31803278ee
|View full text |Cite
|
Sign up to set email alerts
|

Limitations in Molecular Detection of Lymph Node Micrometastasis From Colorectal Cancer

Abstract: Colorectal cancer patients with lymph node metastasis have a shorter survival and may require adjuvant therapy after surgery of the primary tumor. It is supposed that a more reliable diagnosis can be achieved using tumor-specific DNA mutations for the detection of metastasizing cells. To design a practical approach for a molecular diagnosis of micrometastasis, we applied direct DNA sequencing to screen 48 early stage colorectal carcinomas for the most frequent mutations of the KRAS, P53, and APC tumor genes. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Fourth, 1 of 5 cytopathologists was involved in cytology interpretation, in which interobserver variability may have existed. Fifth, direct sequencing has been used for mutation analysis in this study, a method which has been known to exclude mutations present in minor fractions of tumor cells, 44 which may have affected our results.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, 1 of 5 cytopathologists was involved in cytology interpretation, in which interobserver variability may have existed. Fifth, direct sequencing has been used for mutation analysis in this study, a method which has been known to exclude mutations present in minor fractions of tumor cells, 44 which may have affected our results.…”
Section: Discussionmentioning
confidence: 99%
“…In this small series, the concordance rate between the paired cytology and histology sample types was 87.5%. Cases of discordant CRC genotype in primary versus metastatic tumour have been reported in the literature in both nodal as well as solid organ metastases relative to the genotype of the primary tumour 14,15,19 . Possible explanations for this phenomenon, aside from laboratory‐related errors, could be due to a genuine heterogeneity in KRAS genotype within sub‐clones of the primary tumour.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was isolated from 5‐μm thick sections of the formalin‐fixed, paraffin‐embedded resections or cell blocks, or from one entire Diff Quik (DQ)‐ or Papanicolaou (Pap)‐stained smear (for cases 1 and 7) with the QIAamp DNA Micro kit method by Qiagen (Dusseldorf, DE, Germany), according to the manufacturer’s protocol and quantitated by a spectrophotometer. The PCR amplification for the clinically relevant KRAS exons 2 and 3 and BRAF exon 15 were carried out according to published protocols 17,18,19 . The number of sections used and the quantity and quality of DNA extracted before PCR are tabulated in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, perhaps sorting for the more abundant EPCAM + population may improve sensitivity for cancer detection. While previous studies in other cancers have identified micrometastases using RT-PCR, direct Sanger sequencing of specific genes, or histology, our study is the first, to our knowledge, in which whole-exome sequencing has been utilized to prospectively detect and quantify micrometastases in cancer [ 4 , 12 14 ]. Furthermore, while intratumoral heterogeneity has previously been studied in urothelial bladder cancer on a chromosomal level, our analysis is the first to examine this using next-generation sequencing [ 15 ].…”
Section: Discussionmentioning
confidence: 99%